EFFECT OF GROWTH REGULATORS AND PRESERVATIVE SOLUTION ON VASE LIFE AND WATER RELATION OF Gladiolus hybrida L. AFTER CUT FLOWERS - & et al., Al-Hasnawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This experiment was conducted to study the effect of five concentrations of growth regulator of (0, 25 GA3, 50 GA3, 100 Salicylic acid, 150 Salicylic acid) mg.L-1 and three types of preservative solutions on the vase life and water relations for Gladiolus hybrida L. after cut flower. The experiment was conducted as a factorial experiment (3×5) according to Randomized Complete Blocks Design, with three replicates. The results showed that GA3 (50 mg.L-1) significantly excelled in relative fresh weight of 155.33%, absorbed water 59.00 g /flower /day, the lost water 32.99 g /flower /day, water balance 26.01 g /flower /day, vase life 16.96 days, dry weight of flowers 22.89 g, and carbohydrate content in petals 22.34 %, and total carotenoids content in petals 7.84 mg/100 g dry weight. The second solution (5% sucrose + 200 mg.L-1 8.HQS + 200 mg.L-1citric acid) is significantly excelled in most studied traits. The interaction treatment that consisted of (50 mg.L-1 + second solution) is significantly excelled in traits of the relative fresh weight 168.47%, absorbed water 66.32 g/flower /day, the lost water 23.39 g/flower /day, water balance 42.93 g/flower /day, vase life 21.25 days, dry weight of flower 26.11 g, carbohydrate content in petals 20.78% and total carotenoids content in petals 10.06 mg/100g dry weight.